THE PRINCIPLE OF SEPARATION OF POWERS IN THE HISTORY OF THE STATE - Rakhmanov Abdimalik Ergashevich (Scholar Express Journal, 2024)
The article analyzes the emergence of the first buds of the principle of the separation of powers, one of the progressive political theories and democratic traditions, its content enrichment and improvement at different stages of development of human history, and the emergence of its various forms. Also, in the current period of social development, the issues of democratization of society and development towards a highly civilized society based on the new ideological rules of the principle of separation of powers were discussed.
Keywords: Power; statehood; democracy; political liberalism